Factors associated with emotional distress in newly diagnosed prostate cancer patients. Issue 11 (28th January 2015) - Orom, Heather; Nelson, Christian J.; Underwood, Willie; Homish, D. Lynn; Kapoor, Deepak A.
Abstract: Objective: Early identification and intervention have been recommended for newly diagnosed prostate cancer patients who experience significant emotional distress; however, there is little empirical basis for designing or selecting interventions for these men. We sought to identify factors that are associated with distress in these men as a basis for identifying suitable intervention strategies. Methods: Using cross‐sectional data and validated scales, we investigated the extent to which clinical, demographic, belief, and personality characteristics are associated with emotional distress assessed with the Distress Thermometer in 1425 men newly diagnosed with clinically localized prostate cancer (pretreatment). Results: Beliefs potentially amenable to psychoeducational interventions [low self‐efficacy for decision‐making ( B =−0.11, p = 0.02), low confidence in cancer control ( B =−0.03, p < 0.001), and masculine identity threat ( B =−0.26, p = 0.001)] were associated with higher emotional distress, as well as personality factors [low optimism ( B =−0.04, p = 0.052) and low resilience ( B =−0.83, p < 0.001)]. Conclusions: Findings provide a framework for the development of interventions for prostate cancer patients with elevated emotional distress. These may include improving provider communication about prostate cancer prognosis for those with low confidence in cancer control, providing decision‐making support to increase decision‐making self‐efficacy, or referral to brief cognitive behavioral interventions to help patients reframe masculine identity threat or for those with low optimism or resilience reframe and adjust to the health threat. Copyright © 2015 John Wiley & Sons, Ltd.